2022
DOI: 10.1186/s12887-022-03279-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of Lebanese parents towards childhood overweight/obesity: the role of parent-physician communication

Abstract: Background Childhood overweight and obesity is one of the most challenging public health problems facing both developed and developing countries. Several studies carried worldwide assessed predisposing risk factors for childhood obesity, however, few addressed the Middle East region and particularly Lebanon. We aimed in our study to assess factors associated with knowledge, attitude and practice of Lebanese parents regarding childhood overweight, particularly the parent-physician communication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In their study, Woźniak and colleagues showed that providing appropriate education on nutrition to parents can be effective in improving the nutritional status of children at the social level [ 39 ]. The study of Zoghby and colleagues has also shown that better communication between parents and physicians and, as a result, higher awareness of parents about childhood obesity is associated with a better attitude and performance of parents towards childhood obesity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Woźniak and colleagues showed that providing appropriate education on nutrition to parents can be effective in improving the nutritional status of children at the social level [ 39 ]. The study of Zoghby and colleagues has also shown that better communication between parents and physicians and, as a result, higher awareness of parents about childhood obesity is associated with a better attitude and performance of parents towards childhood obesity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the mismatch about BMI was very extreme and this mismatch between doctor's findings and parents' answer was significantly correlated with parents whose kids are overweight. A research study conducted in Lebanon [32] showed that overweight children's parents are less aware and less knowledgeable of their child's weight status and that parent-physician communication has a significant impact on parents' knowledge. In addition, according to a study that appeared in the International Journal of Pediatric Obesity, parents of obese kids were more likely to think that their child's weight was "normal" if the kid had a higher body mass index (BMI) percentile [12].…”
Section: Bmimentioning
confidence: 99%
“…This is in line with a finding which states that the importance of educating parents to achieve better knowledge, attitudes and practices towards obesity is the first step in implementing educational programs and strategies to reduce obesity in children. 27 Health education through family empowerment interventions to prevent and control overweight and obesity is very effective. Increased knowledge about overweight and obesity management also has a positive effect in increasing the role and confidence of families in dealing with children with health problems.…”
Section: Family Knowledgementioning
confidence: 99%